ANALISIS PENGARUH MOTIVASI BERPRESTASI TERHADAP PRODUKTIVITAS KERJA MELALUI KOMUNIKASI ORGANISASI DAN BUDAYA ORGANISASI PEGAWAI DI KAB. JENEPONTO - Misbahuddin, Misbahuddin; Akil, Nashriah (Sekolah Tinggi Ilmu Ekonomi (STIE) Tri Dharma Nusantara Makassar, 2023)
This study aims to determine the effect of Achievement Motivation on Work Productivity through Organizational Communication and Organizational Culture of the State Civil Apparatus in Jeneponto Regency. This research was conducted in Jeneponto Regency. The population in this study were all state civil servants in Jeneponto Regency with ASN samples in Bontoramba, Bangkala, Binamu and Tamalatea Districts totaling 114 State Civil Apparatuses. The sampling technique used saturated sampling. Data collection techniques through observation, interviews, questionnaires and documentation, while data analysis with path analysis. The results of the research findings are that achievement motivation is able to boost the work productivity of civil servants in Jeneponto Regency. The role of intervening variables is very urgent, effective organizational culture.